The Vernacular Typography Analysis on Tombstones in Bandung City: The Typographic And Visual Analysis on Tombstones - Indriani Nur Azizah (KK Komunikasi Visual & Multimedia Fakultas Seni Rupa dan Desain Institut Teknologi Bandung, 2022)
Death is something that all humans have to face. In delivering humans to their final resting place, there are various series of ceremonies that also require property, one of which is a tombstone. Tombstones are a form of respect for those who have died and function as markers and community archives because in them there is information about who died, year of birth and death, service, and position. so that it can be conveyed easily, accurate typography is needed in order to properly represent the information and who is buried there. Therefore this study was formed to find out how the visual form and characteristics of vernacular typography are covered by tombstones through descriptive research. The method of data collection is done by using purposive sampling conducted on 160 samples from several public cemeteries in Bandung. The results show that these tombstones have various variations of vernacular typography which, when grouped, have their own characteristics as a result of the existence of various backgrounds in the society.Keywords : Vernacular, batu nisan, Bandung, typography